PENGARUH FAKTOR NON FISIK TERHADAP PEMBENTUKAN POLA RUANG BANGUNAN PADA RUMOH ACEH DI KABUPATEN ACEH BESAR (The Effect of non-physical factors to form the building space pattern of Rumoh aceh at Aceh Besar) - Farisa Sabila; Antariksa Antariksa; Rinawati P. Handajani (Tesa Arsitektur, 2014)
Aceh Besar is a district which started the development of rumoh aceh architecture in Aceh Province. rumoh aceh has a building space pattern that consists of a ground level, space under the building, and upper space. The concept of building space pattern in rumoh aceh is unique. It introduces a triangular equilibrium of relations between men, God, and the environment. Non-physical factors affect the formation of spatial pattern building on rumoh aceh. The involvement of the Islamic concept affected indirectly the creation of rumoh Acehs spatial pattern. The purpose of this research is to find a non-physical factors which influence the bulding space pattern of rumoh aceh, as well as to find the ideas and knowledge of Rumoh aceh. However, the finding may not rule out the possibilities of further research which implements the concept of aceh rumoh space into a more modern residential space. This research used qualitative descriptive method which performs direct observation of the building space pattern formed, as well as finding the effect on non-phisical factors which are found in the observation area. The formation of the pattern also could be changed by considering the factors of kinship, customs, social, economic, and culture of the Acehnese.